1984
DOI: 10.1152/ajpgi.1984.246.6.g718
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of H+ injury in rabbit esophageal epithelium

Abstract: We previously postulated that active Na transport by the esophageal stratified squamous epithelium is important for maintenance of its barrier function. To investigate this further we studied the effects of HCl on the in vivo esophageal potential difference (PD), on in vitro Na transport, and on esophageal Na-K-ATPase activity. In vivo esophageal perfusion with low concentrations of HCl (20 or 40 mM) increased the PD and a high concentration (120 mM) decreased it. An intermediate concentration (80 mM) caused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
9

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 0 publications
2
77
0
9
Order By: Relevance
“…13,60,63 Chronic exposure to gastric acid and other intra-esophageal materials such as bile and alcohol can disrupt the esophageal barrier function. 63,64 Reduced levels of E2 due to aging, especially, after women's menopause, can potentially increase epithelial permeability and microbial translocation (Fig. 3).…”
Section: Esophageal Epithelial Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,60,63 Chronic exposure to gastric acid and other intra-esophageal materials such as bile and alcohol can disrupt the esophageal barrier function. 63,64 Reduced levels of E2 due to aging, especially, after women's menopause, can potentially increase epithelial permeability and microbial translocation (Fig. 3).…”
Section: Esophageal Epithelial Barrier Functionmentioning
confidence: 99%
“…Such a mechanism of estrogen might explain the male predominance of GERD. [63][64][65] Honda et al 63 conducted an animal study to identify the role of estrogen treatment on the esophageal epithelial barrier function and found that 17β-estradiol administration reduced the dilation of the intercellular space caused by luminal irritants. Moreover, 17β-estradiol administration increased the expression of occludin.…”
Section: Esophageal Epithelial Barrier Functionmentioning
confidence: 99%
“…Both (Orlando, Bryson & Powell, 1984), frog skin (Fischbarg & Whittembury, 1978;Ferreira & Hill, 1982), toad bladder (Wade, Revel & Di Scala, 1973) and rumen (Gemmel & Stacy, 1973;Gaebel, Suendermann & Martens, 1987). In ruminants, a drop in pH and a rise in rumen fluid osmolarity are the consequences of a sudden high intake of easily fermentable carbohydrates and the resulting rumen acidosis (Kezar & Church, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…(Table 2). 16.4 Ϯ 2.1 to 9.9 Ϯ 1.5 mM (n ϭ 13, P Ͻ 0.001). This was accompanied by a very rapid (Ͻ1 min) initial depolarization of V mBL (Fig.…”
Section: Fig 2 Effect Of CLmentioning
confidence: 95%
“…Although the contribution of Cl Ϫ to the short-circuit current is very small, cellular transport of Cl Ϫ , similar to other epithelia, is fundamental for the maintenance of the intracellular milieu. Regulation of cellular Cl Ϫ transport is particularly important in the esophageal epithelium, a tissue regularly exposed to wide fluctuations in luminal content including high levels of NaCl (salt) in food and HCl (gastric acid) due to the reflux of gastric content (14,16). Because very little information is available about Cl Ϫ transport in esophageal epithelial cells, the purpose of this study was to examine its transport pathways across both the basolateral and the apical cell membranes of this epithelium.…”
mentioning
confidence: 99%